How to Evaluate High Level Fusion Algorithms? - Laudy, Claire; Museux, Nicolas (2019 22th International Conference on Information Fusion (FUSION), 2019)
Evaluating high level information fusion algorithms is a tricky problem. Most of the time, situations monitored through high level information fusion are complex, composed of multiple objects or entities, having heterogeneous properties and in relation with each other's. Many criteria have to be taken into account within the evaluation. In this paper, we define several performance evaluation criteria. We focus on criteria related to functional evaluation, namely the correctness, the completeness and the precision of the result, as well as the level of management of uncertainty of information. Our criteria rely on the comparison of the result, given by the evaluated fusion algorithm, with the expected result of a given set of information provided as an input benchmark. We then present a proposition to aggregate them together with the 2-additive Choquet integral to obtain a single evaluation score.